Pengaruh Penambahan Spring Plate dengan Variasi Berat Roller Pulley Primary Terhadap Daya dan Torsi Pada Sepeda Motor 110 Cc - Darul Fikri; Khambali Khambali (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The problem of automatic performance where as the vehicle ages, engine performance will decrease, resulting in the vehicle being difficult to pass uphill terrain because it requires power and torque is needed to make the motorcycle more responsive. This study aims to compare the effect of the addition of spring plates with the variation in the weight of the primary roller pulley on power and torque on 110 cc motorcycles. In this study, using experimental research with quantitative methods, the researcher to obtain the data will conduct tests using a dynotest tool. The addition of a spring plate to the primary pulley affects power and torque. The highest power is produced at a 7-gram roller weight of 5.94 HP and the highest torque produced is 5.65 N.m. Then the highest power is generated at a 9-gram roller weight of 6.12 HP and the highest torque is 5.79 N.m. The highest power is generated at an 11-gram roller weight of 6.04 HP and the highest torque is 5.97 N.m.